ПРИЗНАЧЕННЯ РАЦІОНАЛЬНОГО ПРОЦЕСУ ВИГОТОВЛЕННЯ ТА ВИБІР ЕФЕКТИВНОГО МАТЕРІАЛУ ВІЗКОВОГО ЛИТВА ВАНТАЖНОГО ВАГОНУ (Modern Problems of Metallurgy, 2020)
suggested for making the side frames of freight cars bogies by casting two parts models – the main 20GL and alternative 20G1FL, 30GSL grade steels, which differ in content of alloying components, which have due to this different kinetics of structural formation and, as a consequence, the final structure, which allows for forecasting capabilities varying classes of products strength – K25, K30 and K35, correspondently.
Keywords: freight car, bogie, steel casting, side frame, chemical composition, alloying, kinetics of structural formation, microstructure, mechanical properties, grade of strength.